2022
DOI: 10.17582/journal.aavs/2023/11.1.124.131
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FecXG and FecB Mutations and its Association with Litter Size in Kacang and Boerka Goat

Abstract: The Kacang goat is one of Indonesia's prolific native goat breeds, while the Boerka goat is a crossbreed between Kacang and Boer goats. It is widely known that the ovulation rate and litter size in sheep breeds are significantly impacted by the BMP15 (FecX G ) and BMPR-1B (FecB) gene alterations. Based on this knowledge, the study's objective was to determine the presence of BMP15 and BMPR-1B gene polymorphisms and how they affected the prolific traits of Kacang and Boerka goats. This study indicates that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…Nevertheless, more research is need that reveals the genetic structures of goats in terms of fertility genes. Maskur et al (2023) reported that the mutations of FecX G (c.718C>T) and FecB (c.746A>G) were in Indonesian Kacang and Boerka goats. Another study examining the S32G mutation in the BMP15 gene in 18 breeds of goats, reported a monomorphic structure in Saanen goats (Feng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, more research is need that reveals the genetic structures of goats in terms of fertility genes. Maskur et al (2023) reported that the mutations of FecX G (c.718C>T) and FecB (c.746A>G) were in Indonesian Kacang and Boerka goats. Another study examining the S32G mutation in the BMP15 gene in 18 breeds of goats, reported a monomorphic structure in Saanen goats (Feng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%